Features of phase wave front binary encoding and their potential utilization for alignment purposes (2002)
ABSTRACT: We make use of binary encoding of a phase wave front for the generation of diffractive elements. Binary encoding enables to introduce a constant phase shift between different diffraction orders. We describe the main features of phase wave front encoding and then suggest to apply them for a design of a diffractive alignment element. The proposed positioning tool is a modified version of the hyperbolic zone plate.